Leptin and leptin receptor evaluation in atherosclerotic plaques in patients with type 2 diabetes mellitus - Diana A. Dimitrova ("Consilium Medicum" Publishing house, 2021)
Background. Diabetes mellitus (DM) is a significant predictor of atherosclerosis, cardiovascular disease, and cardiovascular mortality. It is known that atherosclerosis occurs earlier in patients with diabetes, reducing the duration of their life. Leptin as well as other inflammatory markers can contribute to the progression of atherosclerosis in patients with DM, participate in the development of a local inflammatory reaction.